BEBERAPA FAKTOR YANG MEMPENGARUHI KINERJA DOSEN PERGURUAN TINGGI DI KABUPATEN MAROS - -, Sarnawiah (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2016)
Factors affecting the assessment of faculty performance is the ability andmotivation. The research aimed to investigated the effect of the pedagogic,professionalism, personality and social faculity factor lecturer performanceassesment in the higher Education at Maros Regency. Data type in thisresearch is qualitative and quantitative data. Primary data the used in the formof result of obtained kuesioner of higher Education at Maros Regency. Dataanalysed by using multiple linear regression analysis, by using program ofSPSS version 20.0. The results showed that the professional skills andpersonality factors positive and significant impact on performance appraisallecturer at universities in Maros regency. being pedagogic and social skills anda significant negative effect on performance appraisal lecturer at college inMaros Regency. This paper to show professional abilities and personality affecton performance lecturer